Relationship Between Genotype Status and Clinical Outcome in Hypertrophic Cardiomyopathy - Bonaventura, Jiri; Rowin, Ethan J; Chan, Raymond H; Chin, Michael T; Puchnerova, Veronika; Polakova, Eva; Macek, Milan; Votypka, Pavel; Batorsky, Rebecca; Perera, Gayani; Koethe, Benjamin; Veselka, Josef; et al. (Journal of the American Heart Association, 2024)
BACKGROUND: The genetic basis of hypertrophic cardiomyopathy (HCM) is complex, and the relationship between genotype status and clinical outcome is incompletely resolved. METHODS AND RESULTS: We assessed a large international HCM cohort to define in contemporary terms natural history and clinical consequences of genotype. Consecutive patients (n=1468) with established HCM diagnosis underwent genetic testing. Patients with pathogenic (or likely pathogenic) variants were considered genotype positive (G+; n=312; 21%); those without definite disease-causing mutations (n=651; 44%) or variants of uncertain significance (n=505; 35%) were considered genotype negative (G-). Patients were followed up for a median of 7.8 years (interquartile range, 3.5-13.4 years); HCM end points were examined by cumulative event incidence. Over follow-up, 135 (9%) patients died, 33 from a variety of HCM-related causes. After adjusting for age, all-cause and HCM-related mortality did not differ between G- versus G+ patients (hazard ratio [HR], 0.78 [95% CI, 0.46-1.31]; P=0.37; HR, 0.93 [95% CI, 0.38-2.30]; P=0.87, respectively). Adverse event rates, including heart failure progression to class III/IV, heart transplant, or heart failure death, did not differ (G- versus G+) when adjusted for age (HR, 1.20 [95% CI, 0.63-2.26]; P=0.58), nor was genotype independently associated with sudden death event risk (HR, 1.39 [95% CI, 0.88-2.21]; P=0.16). In multivariable analysis, age was the only independent predictor of all-cause and HCM-related mortality, heart failure progression, and sudden death events. CONCLUSIONS: In this large consecutive cohort of patients with HCM, genotype (G+ or G-) was not a predictor of clinical course, including all-cause and HCM-related mortality and risk for heart failure progression or sudden death. G+ status should not be used to dictate clinical management or predict outcome in HCM.
Keywords: mutace; Heart Transplantation; dospělí; Genetic Testing; Genotype; náhlá srdeční smrt; Female; Phenotype; Adult; ženské pohlaví; Death, Sudden, Cardiac; Heart Failure; Time Factors; časové faktory; lidé; srdeční selhání; hypertrofická kardiomyopatie; genotyp; Mutation; genetická predispozice k nemoci; Genetic Predisposition to Disease; Cardiomyopathy, Hypertrophic; prognóza; Risk Factors; Male; progrese nemoci; Aged; Disease Progression; transplantace srdce; rizikové faktory; genetické testování; Prognosis; lidé středního věku; fenotyp; mužské pohlaví; senioři; Middle Aged; Humans